Preservative Effect of Edible Chitosan Coated Liposomes Loaded with Natural Antimicrobial Agents in White Soft Cheese - Sakr, Samah A.; ElShaer, Manal I.; Mohamed, Amina L.; Bayoumi, Mohamed A. (Journal of Advanced Veterinary Research, 2022)
Plainly treated foods are highly recommended in the recent world, so edible packaging using encapsulated essential oils in biopolymers have afforded a premium and nontoxic food preservation technique. In this work, chitosan-based emulsions made of liposomes loaded with thyme essential oil were explored to lengthen the shelf-life of white soft cheese. Chitosan-based emulsions with TEO/liposomes, prepared by 2% wt/v chitosan solutions (CL-TEO), are active for 60 days. Antimicrobial activities were assessed via determination of total viable counts of Bacillus cereus (B. cereus) and Enterococcus faecium (E. faecium) over 4 weeks at refrigerated storage at 5 ÂºC. Cheese samples coated with CL-TEO 2% v/v and samples coated with CL-TEO 1% v/v plus nisin kept its satisfactory appearance, as well acceptable bacterial counts for 1 month at 5ÂºC. The results suggested that the formulated liposomal chitosan emulsions encapsulated TEO 2% v/v and liposomal chitosan emulsion encapsulated TEO 1% v/v plus nisin might be promising natural formulas to extend the shelf life in addition to preserving the flavour of white soft cheese.